Pengaruh Penerapan GCG dan Budaya Tri Hita Karana pada Kinerja Keuangan Lpd Di Kabupaten Jembrana - Astini, Ni Komang Abdi Tri; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 27 No 1 (2019), 2019)
The purpose of this study was to determine the effect of the application of good corporate governance and tri hita karana culture on the financial performance of LPD in Jembrana Regency. This research was conducted in all LPD in Jembrana regency. The number of samples used is 61 LPD, with non probability sampling techniques and saturation sampling methods. Data collection is done through questionnaires and non-participant observation. The analysis technique used is multiple linear regression. The results of hypothesis testing indicate that good corporate governance and the tri hita karana culture partially have a positive effect on the financial performance of LPD in Jembrana regency. This shows that the better implementation of the components of good corporate governance and the tri hita karana culture will be able to improve the financial performance of LPD in Jembrana regency. Keywords : Good corporate governance, tri hita karana culture, financial performance